Do smoking bans always hurt the gaming industry? Differentiated impacts on the market value of casino firms in Macao (China) - Jing Hua Zhang; Kwo Ping Tam; Nan Zhou (Kiel Institute for the World Economy (IfW), 2016)
The gaming economy has expanded rapidly in East Asia during the past decade. Despite the public health hazards of Second Hand Smoking (SHS), smoking bans in casinos remain controversial due to concerns over potential economic losses for casino firms. Applying an event study method, the authors examine the abnormal returns of casino stocks in response to three unexpected announcements of smoking bans in casinos from 2011 to 2015 in Macao. The analysis reveals that the announcements were associated with differentiated abnormal returns of casino stocks. The stocks of the traditional casinos in Macao suffered significant cumulative abnormal losses of 1% to 6%, while the Las Vegas themed casinos in Macao enjoyed significant cumulative abnormal excess returns of 1.4% to 4.8%. Furthermore, the authors find that the low air quality in gaming venues and high dependence on gaming revenues are associated with abnormal losses, while positive management initiatives are significant correlated with positive abnormal returns. This study provides a full picture of the impacts of smoking bans on casinos and will thus be a useful policy reference for the Macao government, as well as for the rapidly growing gaming industry in Asia and other developing economies.
Keywords: L83; K32; Z33; 330; smoking bans; economic impacts; casinos; abnormal return of stocks; Macao